IMPROVING EMPLOYEE SATISFACTION THROUGH TRAINING AND CAREER DEVELOPMENT - Tilova, Nurdinni; Yuliasari, Yuliasari (Yayasan Education and Social Center, 2024)
This study aimed to obtain information on the influence of training and career development on job satisfaction at PT Anggana Catur Prima, North Jakarta, either partially or simultaneously. This type of research uses quantitative methods. The total population is 202 with the sampling technique using the Slovin formula, and the samples obtained in this study amounted to 135 respondents. Data analysis was done using validity tests, reliability tests, classical assumption tests, regression analyses, correlation coefficient analyses, coefficient of determination analyses, and hypothesis testing. The result of this research is that training has a significant effect on job satisfaction, Career Development has a substantial impact on Job Satisfaction, and Training and Career Development simultaneously have a considerable effect on Job Satisfaction. The coefficient of determination is 80%, while other factors influence the remaining 20%